Sustainability in creative and cultural industries: a bibliometric analysis - Kovaitė, Kristina; Šūmakaris, Paulius; Korsakienė, Renata (Creativity Studies, 2022)
The global focus shifts towards sustainable development and makes all the industries to adapt and be active in order to reduce their negative impact on environmental and social environments. The main objective of this study is to provide a coherent overview of current research on sustainability in creative and cultural industries and to highlight possible research streams for future investigations. This is the first study to investigate the scientific publications on sustainability in creative and cultural industries. In total, 247 publications published between 2000 and 2021 and included in Web of Science (Clarivate) were taken into account. The results of this study reveal the following: (1) the increasing trend of publications in the field; (2) the most influential journals, researchers, countries, and articles review; (3) the gaps of extant research and future research directions. The presented study contributes to the scientific fields of business, economics, and communication and the insights are helpful to the researchers and policy-makers in the field of sustainability in creative and cultural industries.